Gingival Retraction Methods for Fabrication of Fixed Partial Denture: Literature Review - Safari S; Vossoghi Sheshkalani Ma; Vossoghi Sheshkalani Mi; Hoseini Ghavam F; Hamedi M (Shiraz University of Medical Sciences, 2016)
Fixed dental prosthesis success requires appropriate impression taking of the prepared finish line. This is critical in either tooth supported fixed prosthesis (crown and bridge) or implant supported fixed prosthesis (solid abutment). If the prepared finish line is adjacent to the gingival sulcus, gingival retraction techniques should be used to decrease the marginal discrepancy among the restoration and the prepared abutment. Accurate marginal positioning of the restoration in the prepared finish line of the abutment is required for therapeutic, preventive and aesthetic purposes. In this article, conventional and modern methods of gingival retraction in the fixed tooth supported prosthesis and fixed implant supported prosthesis are expressed. PubMed and Google Scholar databases were searched manually for studies on gingival tissue managements prior to impression making in fixed dental prosthesis since 1975. Conclusions were extracted and summarized. Keywords were impression making, gingival retraction, cordless retraction, and implant. Gingival retraction techniques can be classified as mechanical, chemical or surgical. In this article, different gingival management techniques are discussed.